Developing of Performance Testing Scheme for Decentralized Domestic Wastewater Treatment Plant in Indonesia - Darwati, Sri; Hastuti, Elis (Proceeding International Conference on Science and Engineering, 2019)
Most of the urban and rural areas in Indonesia still use individual scale of decentralized on-site domestic wastewater treatment such as pit latrines and septic tank. For some building and small community using communal scale of wastewater treatment plant such as fabricated biofilter tank, UASB (up-flow anaerobic sludge blanket), Rotating Biological Contactor (RBC) and wetland. Many application of the decentralized Wastewater Treatment Plants (WWTP) have low performance and the effluent does not meet standard effluent. To ensure the compliance to the regulation, it is necessary to develop the performance testing scheme for decentralized domestic wastewater treatment plant. The objective of the study is to review performance testing scheme in Indonesia, include the legal aspects, existing performance testing procedure for inspection and certification. The target is to develop performance testing schemes consists of testing standard and institutions scheme. The methodology of research are primary and secondary data collection done through field observation and discussion in stakeholder meeting with stakeholder related. The data analysis of this study are comparative study of certification system of decentralized WWTP in Japan, Thailand and Indonesia, descriptive analysis of performance testing method and the role of stakeholders. In conclusion Indonesia has not have regulation regarding certification schemes for decentralized WWTP. The certification schemes is needed to guarantee the WWTP product compliance with the performance standard and effluent standard. The developing decentralized WWTP need the regulation regarding testing body, the provision of performance testing standard, competent testing body, equipment and human resources.